Neurotrophin NGF/TrkA and BDNF/TrkB signaling orchestrates the immune microenvironment in osteosarcoma - Liu, Hongyuan; Wang, Guobing; Wang, Chunxue; Hou, Dan; Li, Shigang; Fan, Yuansheng; Liu, Bing (Frontiers in Immunology, 2026)
Neurotrophin signaling through NGF/TrkA and BDNF/TrkB is increasingly recognized as a driver of osteosarcoma (OS) progression and an organizer of its immune milieu, yet clinical translation has lagged amid intratumoral heterogeneity and a myeloid-skewed, vasculature-aberrant tumor microenvironment (TME). Features that blunt immune competence include dominant tumor-associated macrophage programs, sparse and dysfunctional effector T cells, endothelial remodeling that restricts lymphocyte entry, and neuron–immune circuits that reinforce suppression. Within this context, NGF/TrkA promotes matrix remodeling, monocyte ingress, and macrophage polarization, while BDNF/TrkB modulates dendritic-cell maturation, supports survival and angiogenesis, and may condition T-cell priming—together positioning neurotrophins as coordinators of tumor persistence and immune exclusion. This review surveys these mechanisms and maps them to therapeutic strategies: kinase-level blockade with approved TRK inhibitors in NTRK fusion–positive disease; exploratory pathway inhibition in fusion-negative OS; ligand-directed approaches; and rational combinations with immunotherapy and vascular/stromal modulators. We highlight biomarker frameworks (receptor–ligand activity scores, phospho-Trk immunohistochemistry, NGF–MMP-2 readouts) and safety considerations that should structure early-phase trials. Clinical and preclinical signals collectively support testing neurotrophin-targeted strategies to recalibrate myeloid composition, enhance antigen presentation, and restore T-cell access to tumor beds. The purpose of this review is to synthesize current evidence and propose a translational roadmap for targeting NGF/TrkA and BDNF/TrkB to remodel antitumor immunity in osteosarcoma.